2004
DOI: 10.1111/j.1469-0691.2004.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of Helicobacter pylori infection in non-institutionalised children with mental retardation

Abstract: Eighty-four children with mental retardation (34 boys, 50 girls; age range 2-18 years, median 6 years) and 84 age- and gender-matched outpatient controls were studied. All children were living at home, had never stayed in an institution, and came from the same urban area. Seropositivity for Helicobacter pylori was found in 42 (50%) of 84 mentally retarded children and 16 (19%) of 84 controls (p < 0.01). Socio-economic factors did not differ between the two groups. The findings indicated that a higher prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…The present study reveals that institutionalization within rehabilitation centers is not a predictor for G. lamblia or H. pylori among mentally challenged individuals in Alexandria, Egypt. Our finding is in line with Luzza et al [42], who reported that H. pylori is highly prevalent among mentally challenged children, irrespective of their institutionalization status. In contrast, Wallace et al [43] reported that past or current institutionalization of intellectually disabled adults is an environmental risk factor associated with H. pylori infection.…”
Section: Discussionsupporting
confidence: 93%
“…The present study reveals that institutionalization within rehabilitation centers is not a predictor for G. lamblia or H. pylori among mentally challenged individuals in Alexandria, Egypt. Our finding is in line with Luzza et al [42], who reported that H. pylori is highly prevalent among mentally challenged children, irrespective of their institutionalization status. In contrast, Wallace et al [43] reported that past or current institutionalization of intellectually disabled adults is an environmental risk factor associated with H. pylori infection.…”
Section: Discussionsupporting
confidence: 93%
“…They reported that 50% of the patients were seropositive, which was confirmed by C-UBT test in 95%. Luzza et al also studied 42 children with Down syndrome (34 males and 50 females 2-18 years) in terms of H. pylori in 2004 and concluded that 50% of the patients were seropositive which was confirmed by C-UBT test in 95%, while in the current study 54.6% were seropositive, and it was also confirmed by C-UBT test (12). Considering that UBT is an expensive test, in the first step the current study used ELISA test then UBT test was used to confirm the positive cases.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, H. pylori can cause ischemic heart disease (IHD), chronic obstructive pulmonary disease (COPD), iron deficiency anemia (IDA), cerebral and neurological disease such as Alzheimer and migraine (9)(10)(11). Owing to the fact that patients with Down syndrome have genetic defects and physical problems, it seems vital to prevent the prevalence of infection among them; hence, early detection of the infection in such patients can prevent the spread of it (12). Due to the life condition of the institutionalized children, transmission of H. pylori can occurred easily; therefore, it is a serious matter to recognize and determine transmission risk factors of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to infections increases risks during chemotherapy, counteracting the increased DS cancer cell susceptibility to drugs 72 . Also, this potentially explains the increased rates of stomach cancer in some studies, despite the gastric cancer-associated trefoil factor (TFF) family of tumour suppressor genes being on HSA21, as these genes are silenced by Helicobacter pylori infection 73 , and there is evidence of higher rates of H. pylori infection in DS 74,75 .…”
Section: Ds Biology Predicts Cancer Pronenessmentioning
confidence: 99%